2014
DOI: 10.1007/s11157-014-9357-z
|View full text |Cite
|
Sign up to set email alerts
|

Requirements and boundary conditions for fish passes of non-sport fish species based on Chilean experiences

Abstract: Most artificial fish passes have been developed in Northern temperate rivers and are designed to serve large, migratory sport fish species (mostly salmonids). Experience in construction and maintenance of fish passes show that salmon-criteria are not adequate for flat-land rivers and non-sport fishes. Consequently, over the last decade, design criteria have changed to take requirements of target species into account. Extrapolation of these concepts to rivers in the Southern Hemisphere with different hydrologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 42 publications
0
35
0
2
Order By: Relevance
“…‘Non‐sport fish’ is a term used to describe freshwater species with small body size (<150 mm total length when adults), which is the case for most native species in temperate regions of the Southern Hemisphere (e.g. Boubée et al ., , for New Zealand species and Link and Habit, , for Chilean species). Because of their small body size, they are generally not commercially important, but several are endemics and have high conservation value (Habit et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…‘Non‐sport fish’ is a term used to describe freshwater species with small body size (<150 mm total length when adults), which is the case for most native species in temperate regions of the Southern Hemisphere (e.g. Boubée et al ., , for New Zealand species and Link and Habit, , for Chilean species). Because of their small body size, they are generally not commercially important, but several are endemics and have high conservation value (Habit et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Absent of a biological imperative to migrate to distant spawning locations, resident non‐recreational fish may not make the potentially stressful journey upstream through technical fishways. Thus, we follow Link and Habit () in recommending nature‐like bypasses to ensure habitat continuity for these species where there is sufficient space for a low‐gradient structure. Some commentators have suggested that nature‐like bypasses are also an appropriate solution for migratory fish, but they often fail in this regard due to poor attraction (Bunt et al., , ; Noonan et al., ; Kemp, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true of small‐bodied, non‐recreational species (e.g. adults <150 mm TL; Link & Habit, ), whose relatively weak swimming abilities are consistent with their diminutive stature (Bestgen, Mefford, Bundy, Walford, & Compton, ; Ficke, Myrick, & Jud, ; Laborde et al., ; Leavy & Bonner, ; Nelson, Gotwalt, Simonetti, & Snodgrass, ; Nikora, Aberle, Biggs, Jowett, & Sykes, ). Several of these species support culturally and economically important capture fisheries (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish passage research remains largely entrenched in the early paradigm of salmonid biology. This long‐standing focus has resulted in the same approach being perpetuated all over the globe, for all species, in all geographical contexts, rather than taking a step back and rethinking whether it is the right approach in a particular location (Link & Habit, ; Mallen‐Cooper & Brand, ; Wilkes, Baumgartner et al, 2018). Despite the significant differences between the requirements of salmonids and most other fishes (Figure ), including those from the tropics and temperate Southern Hemisphere, the knowledge, techniques, thinking and solutions developed from studies of salmonids have been widely transferred to fish passage design and management elsewhere (Silva et al, ).…”
Section: Biases In Fish Passage Research and Applicationmentioning
confidence: 99%